STATISTICAL LITERACY ABILITY OF BOARDING AND NON-BOARDING STUDENTS AT MAN 1 SURAKARTA - wijaya, arif safta; Swastika, Annisa (Prima: Jurnal Pendidikan Matematika, 2024)
Boarding and non-boarding students have differences in their daily activities, so there is a possibility that the statistical literacy skills between boarding and non-boarding students at MAN 1 Surakarta are different. Statistical literacy ability is the ability to read involving interpretation of data and understanding of available information. This study used a qualitative descriptive method where the researcher used test and interview techniques which were conducted on boarding and non-boarding students at MAN 1 Surakarta, with the sample used being 46 class XI students with a comparison of 23 boarding students and 23 non-boarding students. the purpose of this study is to describe statistical literacy skills between boarding and non-boarding at MAN 1 Surakarta. The results of this study indicate that the abilities of boarding and non-boarding students at MAN 1 Surakarta are not evenly distributed, with indicators of statistical literacy ability namely understanding data, interpreting data, and communicating data. boarding and non-boarding students have the ability to understand data well, but boarding and non-boarding students have poor data interpretation skills, besides that boarding students have the ability to communicate graphical data better than non-boarding students, but the ability to communicate data in Sentence forms of boarding and non-boarding students at MAN 1 Surakarta have very good abilities.